IMPLIKATUR KONVENSIONAL DAN NON KONVENSIONAL TUTURAN PENGUNJUNG KAWASAN LAWANG SEWU SEMARANG JAWA TENGAH - Ika Arifianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
The speech of visitors of the Lawang Sewu Semarang  is very interesting to study, because the average Lawang Sewu visitors come from outside of Semarang with diverse languages and social and educational backgrounds.  The way they deliver utterances is very diverse.  The use of implicature in language does not mean that it is not intentional or does not have a specific function. The use of implicature in language has considerations such as to refine speech, maintain ethics of politeness, to insinuate subtly (indirectly), and to avoid offending directly.  In implicative speech, the speaker and the interlocutor must have the same concept in a context.  There are conventional implicative forms of speech by visitors of Lawang Sewu area.  Conventional implications are the meanings of utterances that are conventionally or generally accepted by the public.  The approach used in this study is twofold, namely the theoretical research approach of nonconventional implications as expressions that imply something different from the actual and methodological esearch approach. The theoretical approach is used to test pragmatic analysis as the study.  The methodological research approach used is descriptive-qualitative method.